Strategi Efektif dalam Inventarisasi dan Pemeliharaan Sarana Prasarana Pendidikan - Mardi; Sukron Makmun; Haikal Marif (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Effective management of educational facilities and infrastructure plays a crucial role in supporting the quality of learning and ensuring the sustainability of educational activities. However, many schools still encounter various challenges, including inaccurate inventory records, inadequate routine maintenance, and limited human and financial resources. This study aims to examine strategies for inventory management and maintenance of educational facilities through a literature review approach. Data were collected from accredited academic journals, educational management textbooks, and relevant national education regulations. The findings indicate that effective management strategies include the implementation of digital-based data collection systems, systematic asset classification, preventive maintenance practices, and the involvement of administrative staff as well as external technical personnel. Furthermore, emerging challenges in facility and infrastructure management can be addressed through principal-led policies, continuous staff training, and active participation of the school community. The results of this study provide both conceptual and practical contributions for educational institutions in developing a sustainable, transparent, and accountable asset management system that supports the improvement of educational quality